Reliability improvement of frame-based equipment for ultra-reliable and low latency communication in unlicensed spectrum. (22nd February 2022) - Chen, Hsueh-Yi; Wang, Sheng-Shih; Sheu, Shiann-Tsong
Based on frame-based equipment (FBE), the 3GPP Release-17 has considered user equipment-initiated channel occupancy time to enhance ultra-reliable and low latency communication (URLLC) under the controlled environment, where all devices operating on the unlicensed spectrum and unexpected coexisting interference only sporadically happens. However, as the presence of interference sources (e.g., Wi-Fi) increases accidentally, the URLLC reliability rapidly decreases. This paper proposes a transmit/receive switching scheme, which considers the busy tone transmission to reduce the coexisting interference. We also introduce four policies based on channel quality to balance the URLLC reliability and the impact on Wi-Fi. Moreover, this paper proposes a fixed frame period offset adjustment scheme to increase the spectrum efficiency and further enhance the FBE reliability. Simulation results showed that, compared to the method only using the legacy FBE, the technique using the proposed schemes significantly achieves a higher reliability for URLLC transmissions, especially in the high interference environment.